Design and development of prototype robot gripper for object weight measurement - Almassri, Ahmed M. M. (2014)
Robotic gripper is a mechatronic machine that is made to complete tasks whenever it is required, especially for repetitive and dangerous tasks as well as specific applications, such as military robots, automotive industries and medical operations. Such mentioned tasks, require a lot of labor force for the assembly line and material handling. Therefore, there is a significant need to have a dedicated machine, which is suitable for this application as a safety concern. This is difficult to be obtained without equipping the robotic gripper with some types of sensors. A few technologies have been used different types of sensors in order to measure the forces between the claw of robotic gripper and an object. A good example is a pressure sensor, which is commonly used in the robotic gripper operations, especially to grasp any object. However, the existing robotic gripper has never been introduced the weight measurement method while grasping object based on piezoresistive pressure sensor. In this research, many works are focused to overcome the weaknesses in the current design applications such as the pressure range of sensor. Therefore, this study has proposed a robotic gripper prototype with a new configuration of pressure sensor distribution, based on development of grasping algorithm for object’s weight measurement. The new configuration of pressure sensors will be based on the proposed modified Wheatstone Bridge Circuit WBC as it has a high sensitivity as well as capability for grasping mechanism and weight measurement. The proposed work also includes the development of new algorithm for data extraction and signal conditioning analysis that will be loaded into the microcontroller system. As a result, a new approach of pressure sensor distribution on the robotic gripper prototype has been developed with proposed modified WBC and grasping algorithm with 0.982 sensitivity and 98.4% efficiency. Along with the new features of this prototype system, the combination of grasping and weight measurement is significantly improved when it is compared with the existing one.